1997
DOI: 10.1046/j.1471-4159.1997.68020578.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Promotes Apoptosis in Cerebellar Granule Cells by Inhibiting the Trophic Effect of NMDA

Abstract: When primary cultures of cerebellar granule neurons are grown in a physiological concentration of KCl (5 mM) they undergo apoptosis, which can be prevented by growing the cells in the presence of N‐methyl‐d‐aspartate (NMDA). We now show that ethanol inhibits this trophic effect of NMDA, i.e., promotes apoptosis, and also inhibits the NMDA‐induced increase in intracellular Ca2+ concentration in cells grown in 5 mM KCl. Both effects of ethanol show a similar concentration dependence and are reversed by a high co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
81
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(90 citation statements)
references
References 32 publications
9
81
0
Order By: Relevance
“…In agreement with previous reports performed on granule cells from 8-day-old rat, we observed that ethanol provokes apoptosis of granule neurons in primary culture (25). The ethanol-induced neuronal death exhibited the characteristic features of apoptosis including cell shrinkage, nuclear condensation, and DNA fragmentation (26).…”
Section: Effects Of Pacap On Ethanol-induced Granule Cell Apoptosissupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with previous reports performed on granule cells from 8-day-old rat, we observed that ethanol provokes apoptosis of granule neurons in primary culture (25). The ethanol-induced neuronal death exhibited the characteristic features of apoptosis including cell shrinkage, nuclear condensation, and DNA fragmentation (26).…”
Section: Effects Of Pacap On Ethanol-induced Granule Cell Apoptosissupporting
confidence: 92%
“…It has been established that ethanol induces cell death by inhibition of N-methyl-D-aspartate receptor function (6,25,42). In particular, during a critical period of brain development, ethanol impairs N-methyl-D-aspartate-mediated brain-derived neurotrophic factor expression, leading to excessive granule cell loss (6,43,44).…”
Section: Effects Of Pacap On Ethanol-induced Granule Cell Apoptosismentioning
confidence: 99%
“…This suggests that added D-serine in conjunction with glutamate, spontaneously released from vesicles in S-K5 (Mellor et al, 1998), is able to activate NMDAR. The finding that glycine (100 lM) has no detectable effect on apoptosis and on survival promoting activity of NMDA (Bhave & Hoffman, 1997) suggests that NMDAR complex is more sensitive to D-serine than to glycine.…”
Section: Discussionmentioning
confidence: 99%
“…However, targets of ethanol, and the subsequent signal transduction pathways, which lead to the mitochondrial apoptotic pathways, are largely unknown. Previous studies using cultured neurons indicate that ethanol perturbs functions of neurotrophic factors (such as brain-derived neurotrophic factor and insulin-like growth factor-I) probably through blockade of NMDA receptors [7][8][9] leading to the inhibition of PI3K [8,9]. The suppression of Akt [4] and activation of GSK-3 [10], downstream effects of PI3K inhibition, have also been reported in the developing brain exposed to ethanol.…”
Section: Introductionmentioning
confidence: 99%